A Case Study of a Child with ASD in a Regular Preschool in the United Arab Emirates - Hammouda, Ghada (2005)
The case study examines the progress of a child with ASD who is included in a regular pre-school in a city in the UAE ( United Arab Emirates) without specialized support. An insight into the context to this child’s inclusion is also examined. It is hoped that this study answers the main research question: what are the effects of inclusion in a regular preschool in the UAE on a child with ASD? In order to answer such a question, a thorough follow up of the child’s IEP (Individualised Educational Plan) is undertaken. Insights into the context are used to put forward research-based recommendations that may improve the effectiveness of inclusion in this situation. Qualitative research methods such as observations, interviews and document analysis were used for this investigation. However, a group of methodological issues and problems occurred and were acknowledged and dealt with accordingly. The study ends with research-based recommendations for future practice.